DEMOKRATISASI TEORI ORGANISASI MENURUT PERSPEKTIF POSTMODERNISME - Soemarno, Soemarno (Universitas Muhammadiyah Magelang, 2004)
Modernisme theory model, such as autrocratic, custodial, supportifand kolegial, is an organization theory which can fulfill the human needs more than tha last 100 year. With the end modernism life cycle, then appear a new merk, postmodernisme have 3 version organization theory that is postbureaucacy, philosophy meddling with periodic and de differentiation. Based on the tend of democratic model which ove continue, so the Z theory is an organization theory, which is the form of integration organization theory and supportif model with kolegial, between the typical of success Japan's company and American's culture, is a postmodernisme organization which the form and the concrete democratic characteristic from postmodernisme perspectif. Postmodernisme and the Z theory is interrelated together, without put asied with the weakness.